Penerapan Arsitektur Neo-Vernakular pada Museum Arkeologi di Mojokerto : Integrasi Budaya & Modernitas - Tiara Putri Widyawati; Muchlisiniyati Safeyah (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2026)
The Mojokerto Archaeological Museum, known as an architectural object that has a wealth of history and culture, especially from the heyday of the Majapahit Kingdom, is the right location for a case study. This study aims to explore how local architectural elements, such as traditional forms, materials, and spatial arrangements, can be combined with modern functional and aesthetic needs. The research method used is qualitative which aims to obtain information directly through field observations and analysis of related literature studies. Thus, the museum does not only function as a place to store artifacts, but also as a space that represents a dialogue between the past and the present that is integrated into traditional values and modern innovations through the application of local architectural elements. This study shows that the Neo-Vernacular architectural approach is able to create a balance between traditional values and modern design, producing optimal educational and recreational spaces, supporting social interaction, and providing a satisfying experience for visitors. This study is expected to make a significant contribution to the development of sustainable architecture that respects cultural heritage, while meeting the aesthetic and functional demands of contemporary society.